Spirituality, Social Support, and Quality of Life: A Study of Indonesian Christian Patients with End-Stage Renal Undergoing Haemodialysis Treatment - Maria Magdalena Dwi Wahyuni; Anderias Umbu Roga; Eka Wilda Faida; Fahira Marsanda Alkatiri; Rambu Kezia Tamu Ina Palandima (JURNAL INFO KESEHATAN, 2026)
Spirituality and social support are recognized as important determinants of quality of life (QoL) among patients with chronic illness. In Indonesia, where religious values are deeply embedded in daily life, understanding these factors is essential for developing culturally appropriate care for Christian patients with end-stage renal disease (ESRD). This study aimed to examine the relationship between spirituality, social support, and QoL among Indonesian Christian ESRD patients undergoing hemodialysis at Prof. Dr. W.Z. Johannes Hospital, Kupang, East Nusa Tenggara. A cross-sectional design was employed involving 176 participants. Social support, spirituality, and QoL were measured using the Multidimensional Scale of Perceived Social Support (MSPSS), the Daily Spiritual Experiences Scale (DSES), and the WHOQOL-BREF, respectively. Data were analyzed using multiple linear regression to obtain adjusted β coefficients and 95% confidence intervals (CI). The results showed that spirituality was significantly associated with QoL (β = 0.29; 95% CI: 0.22–0.36). Social support also demonstrated a significant positive relationship with QoL after adjustment for confounding variables (β = 0.42; 95% CI: 0.34–0.50). In conclusion, higher levels of spirituality and social support are associated with better QoL among Christian ESRD patients undergoing hemodialysis. These findings highlight the importance of integrating spiritual care and strengthening social support systems in the management of ESRD patients.